Workload and turnover intention among gen z bank empoyees: the moderating roles of flourishing and emotion regulation - Prisca Yulina Prameswari; Rostiana Rostiana; I Made Budiana (Jurnal Konseling dan Pendidikan, 2025)
Digital transformation in the banking sector has intensified the responsibilities and pace of work, increasing workload among Generation Z employees and potentially heightening turnover intention. This study examined the relationship between workload and turnover intention, as well as the separate moderating roles of flourishing and emotion regulation. A correlational non-experimental design was used, employing Moderated Regression Analysis (MRA), with questionnaire and convenience sampling. Participants consisted of 226 Gen Z bank employees in Indonesia, aged 20–27 years, with a minimum of six months work experience. The results showed that workload was positively and significantly assosiated with turnover intention (r = 0.397; p < 0.05), both flourishing and emotional regulation have a significant negative relationship with turnover intention. Moderation analysis showed that flourishing (β = -0.395 p < 0.05) and emotion regulation (β = -0.308; p < 0.05) reduced the strength of the relationship between workload on turnover intention. The highest turnover intention was found among employees with high workload and low flourishing or emotion regulation. These findings supported the Job Demand-Control theory and emphasized the importance of psychological well-being and emotional skills in reducing turnover intention.